Sustainable Tourism Development of Patong Beach Phuket Province - สิงห์ฆาฬะ, สุเทพ (Journal of Humanities and Social Sciences, Rajapruk University, 2019)
This research aims to study and compare the level of reviews of tour operators continue to sustainable tourism development in the overview based on the marital status of personnel and to set guidelines for sustainable tourism development of Patong Beach Phuket Province. By having a sample of 2 groups as follows: 1) tour operators, accommodation business and recreation business by questionnaire of 315 and 2) sample that is used in the interview 5 people including the local administration Patong municipality, Phuket Province 2 people and stakeholders 3 people. The data were analyzed using statistical frequency distribution, percentage, mean, standard deviation, t-test, One-way ANOVA and qualitative data using content analysis. The results showed that; The sustainable tourism development of Patong beach Phuket Province the overall rating is based on a massive scale and when considering a list of aspects found to below average the satisfaction of tourists, the benefits of tourism, natural resource, planning and management and the quality of the environment is moderate. The tour operators’ opinion comparison found that male opinions on sustainable tourism development than female in the management plan the quality of the environment and the satisfaction of tourists statistically significant at the .05 level. The age found to have comments on the sustainable development of tourism does not different. The study found that tour operators with different education background had opinions on sustainable tourism development in natural resources, planning and management, and the quality of the environment the statistical significance .05 level. And found that the overall of tour business with less than business accommodation and less than business recreation had different at .05 significant. The tourism development of Patong beach Phuket Province to include sustainability create a new tourist attraction in the municipality of Patong such as the Ban Mon community, Wang Kee on Waterfall, Nanai community, Chaiwat community, Parkbang community. Provide Halal village project (Halal Village) at Ban Kalim Patong, low carbon city (Low Carbon), such as the campaign for the bicycle, establishment of conservation Club of Patong beach and editor urban planning law, appropriate, consistent with the growth of the town in the future.